Оценка механизма координации системы планирования - Хращевский, Р.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The assessment mechanism to coordinate the planning system. The possibility of
well-coordinated system with large external and internal factors.